The role of serum anti-Mullerian hormone in assessment of ovarian function in infertile women in Kirkuk - M. Marbut, Mossa; Omer Ibrahim, Razaw; Khedher Ghalib, Ayla (Tikrit Journal of Pharmaceutical Sciences, 2023)
Antimullerian hormone (AMH) is known as mullerian inhibiting substance (MIS), is produced by granulose cells from 36 week of gestation until menopause. AMH is produced by the ovarian follicles & its levels are used to assess the number of antral follicles in the ovaries. The AMH test is used more & more because the level of AMH do not change significantly throughout the menstrual cycle & can be measured anytime during the menstrual cycle. The aim of the study is to investigate the role of AMH in assessment of ovarian reserve in infertile women in Kirkuk. A cross sectional study was conducted in Kirkuk governorate from first of November to the end of January. This study includes 62 women (20 fertile women as control & 42 infertile women without polycystic ovary). Blood samples were taken at day 2 of menstrual cycle. Serum FSH concentration was measured by using ELISA. While, AMH was measured by using AMH/MIS enzyme linked immunosorbant assay kit (Immunotest material USA). There are no significant differences regarding BMI & age between infertile patients as compared with control fertile women. The serum FSH of infertile women was found significantly higher than that of control fertile women. The concentration of serum AMH of infertile women was significantly lower than that of fertile control women. In the infertile group, there is a significant inverse relationship between serum AMH concentrations & serum FSH concentration, ( r=0.3, p p≤0.05). Also, there is a negative inverse relationship between serum concentration of AMH & age of infertile patients, (r=0.368; p≤0.01). Moreover, there is a positive relationship between serum FSH & age in infertile women (r=0.43; p≤0.01).